2013
DOI: 10.5435/jaaos-21-04-204
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Repair

Abstract: Historically, treatment of meniscus tears consisted of complete meniscectomy. Over the past few decades, however, the long-term morbidities of meniscal removal, namely the early development of knee osteoarthritis, have become apparent. Thus, management of meniscal tears has trended toward meniscal preservation. Recent technological advances have made repairs of the meniscus easier and stronger. In addition, adjunctive therapies used to enhance the healing process have advanced greatly in the past few years. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
105
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 47 publications
1
105
0
5
Order By: Relevance
“…Such findings have led to a renewed focus on meniscal preservation strategies to prevent articular cartilage degeneration. Recent efforts have been directed toward repair or enhancement rather than resection of the injured meniscus [6,11,13,17,[20][21][22]26]; however, even with the best techniques, meniscus repairs can fail. Newer options for meniscus transplantation and tissue engineering have shown some promise, but current evidence regarding long-term outcomes compared with meniscus repair is lacking [5,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings have led to a renewed focus on meniscal preservation strategies to prevent articular cartilage degeneration. Recent efforts have been directed toward repair or enhancement rather than resection of the injured meniscus [6,11,13,17,[20][21][22]26]; however, even with the best techniques, meniscus repairs can fail. Newer options for meniscus transplantation and tissue engineering have shown some promise, but current evidence regarding long-term outcomes compared with meniscus repair is lacking [5,26].…”
Section: Introductionmentioning
confidence: 99%
“…It is theorized that higher levels of platelets can allow for release of growth factors, which may promote angiogenesis and soft tissue healing. The standard for meniscus repair involves an inside-out vertical mattress suture configuration [17,22]. The PRP clot can be sutured into the repair site and delivered under direct visualization.…”
Section: Introductionmentioning
confidence: 99%
“…I numerosi studi biomeccanici ed epidemiologici sul ruolo dei menischi e sulla loro capacità riparativa legata soprattutto alla vascolarizzazione, hanno dimostrato la necessità di preservare queste strutture per la loro funzione di "shock absorber", trasmissione dei carichi, propriocettiva e di stabilizzazione del ginocchio [36][37][38][39][40]. In virtù di questi aspetti, le tecniche di riparazione meniscale hanno subito negli ultimi anni un' evoluzione che ha prodotto una chiara diversificazione, in modo da offrire al chirurgo ortopedico molte possibilità di intervento.…”
Section: Discussioneunclassified
“…Le tecniche inside-out si sono succedute e affiancate alle suture outside-in e alle all-inside di prima e seconda generazione [31]. Ad oggi non esistono evidenze scientifiche che dimostrino la superiorità assoluta di una tecnica rispetto all'altra, ma ognuna possiede indicazioni specifiche in base alla zona di lesione [37,41]. Le indicazioni e la prognosi di una sutura meniscale sono legate a specifici fattori come il tipo di lesione, la localizzazione, la cronicità, l'età del paziente e il supporto vascolare.…”
Section: Discussioneunclassified
“…9 Most of these reports do not separate groups based on medial or lateral or degenerative or nondegenerative tears, nor do they separate groups based on whether or not a concomitant ACL reconstruction was performed at the time of meniscal preservation surgery. Shelbourne and Carr 10 found that the results of medial meniscus (MM) repair versus partial meniscectomy at the time of ACL reconstruction relied heavily on whether or not the tear was degenerative.…”
mentioning
confidence: 97%